The role of intraspecific trait variation in driving post‐metamorphic survival: Implications for recruitment in open populations - Luis Giménez; Stuart R. Jenkins (Ecology and Evolution)
Abstract Most ecological studies attempting to understand causes of population dynamics and community structure disregard intraspecific trait variation. We quantified the importance of natural intra‐cohort variation in body size and density of juveniles for recruitment of a sessile marine organism, the barnacle Semibalanus balanoides. Barnacles are representative of species organised in metapopulations, that is, as open local populations connected by larval dispersal. We tracked the individual growth and survival of a cohort of juvenile barnacles from two shores of North Wales. Barnacles settled as larvae in spring of 2002 on previously cleared rock. The density of these new recruits was experimentally manipulated in June and randomly selected individuals were monitored from June to October to evaluate the role of barnacle size and density in predicting survival. In doing so we characterised density at three spatial scales (quadrat: 25 cm2, cells within quadrats: 25 mm2 and neighbourhood: number of neighbours in physical contact with the target barnacle). At all scales, variations in juvenile body size exacerbated the effect of density‐dependent mortality on population size. While density‐dependent mortality was very intense in the small‐sized individuals, large‐sized individuals experienced very weak density‐dependent mortality and showed high survival rates. Using the concept of ‘Jensen inequality’, we show that important biases in estimations of survival, based on population size only, occur at high barnacle densities, where survival is low. Our study highlights the role of body size variation in understanding dynamics of open populations.